Honokiol inhibits melanoma stem cells by targeting notch signaling. Issue 12 (9th December 2014) - Kaushik, Gaurav; Venugopal, Anand; Ramamoorthy, Prabhu; Standing, David; Subramaniam, Dharmalingam; Umar, Shahid; Jensen, Roy A.; Anant, Shrikant; Mammen, Joshua M.V.
<x xml:space="preserve">Abstract</x> Melanoma is an aggressive disease with limited therapeutic options. Here, we determined the effects of honokiol (HNK), a biphenolic natural compound on melanoma cells and stemness. HNK significantly inhibited melanoma cell proliferation, viability, clonogenicity and induced autophagy. In addition, HNK significantly inhibited melanosphere formation in a dose dependent manner. Western blot analyses also demonstrated reduction in stem cell markers CD271, CD166, Jarid1b, and ABCB5. We next examined the effect of HNK on Notch signaling, a pathway involved in stem cell self‐renewal. Four different Notch receptors exist in cells, which when cleaved by a series of enzymatic reactions catalyzed by Tumor Necrosis Factor‐α‐Converting Enzyme (TACE) and γ‐secretase protein complex, results in the release of the Notch intracellular domain (NICD), which then translocates to the nucleus and induces target gene expression. Western blot analyses demonstrated that in HNK treated cells there is a significant reduction in the expression of cleaved Notch‐2. In addition, there was a reduction in the expression of downstream target proteins, Hes‐1 and cyclin D1. Moreover, HNK treatment suppressed the expression of TACE and γ‐secretase complex proteins in melanoma cells. To confirm that suppression of Notch‐2 activation is critical for HNK activity, we overexpressed NICD1, NICD2, and performed HNK treatment. NICD2, but not NICD1, partially restored the expression of Hes‐1 and cyclin D1, and increased melanosphere formation. Taken together, these data suggest that HNK is a potent inhibitor of melanoma cells, in part, through the targeting of melanoma stem cells by suppressing Notch‐2 signaling. © 2014 Wiley Periodicals, Inc.